Figure di identità. La lettera-immagine come espressione dell'identità di prodotto - Valeria Bucchetti (Ocula)
Through the analysis of some exemplary cases referred to the field of packaging design, we want to investigate how the typeface generates identity figures that modify the status of fonts, making them play the role of images capable of activating processes of meaning and narratives consistent with the reference world of the product. This is what happens in the primary area of the packaging, on the facing of those packaged products which delegate the construction of their identity to a communication system based solely on the word - on the alphabetic element - thus acting on a verb-iconic register in which the two polarities (verbal and iconic) find a perfect fusion.